2023
DOI: 10.1039/d2tc04600h
|View full text |Cite
|
Sign up to set email alerts
|

Assembling a high-performance asymmetric supercapacitor based on pseudocapacitive S-doped VSe2/CNT hybrid and 2D borocarbonitride nanosheets

Abstract: Construction of high-performance asymmetric supercapacitors is vital for achieving a sustainable energy storage model. Layered 2D materials are considered to be a pivotal contributing factor to the modern-day energy storage...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…In both studies mentioned above, the synthesized BCN showed a 2D sheet‐like morphology with ample electrochemical active edges, which was fruitful in their supercapacitor performance. [ 36 ] However, the electrochemical performance of Zou et al synthesized BCN 3D network outranked the above studies by replacing the precursors with melamine foam‐derived carbon skeleton, providing higher surface area and as a reservoir for electrolytic ion intake. However, the solvent‐free BCN network was synthesized through two‐step methods: ball milling of B 2 O 3 , dicyandiamide, and polyvinylpyrrolidone and afterward transferring it for pyrolysis at 1050 °C in the presence of H 2 /N 2 .…”
Section: Methods Of Bcn Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…In both studies mentioned above, the synthesized BCN showed a 2D sheet‐like morphology with ample electrochemical active edges, which was fruitful in their supercapacitor performance. [ 36 ] However, the electrochemical performance of Zou et al synthesized BCN 3D network outranked the above studies by replacing the precursors with melamine foam‐derived carbon skeleton, providing higher surface area and as a reservoir for electrolytic ion intake. However, the solvent‐free BCN network was synthesized through two‐step methods: ball milling of B 2 O 3 , dicyandiamide, and polyvinylpyrrolidone and afterward transferring it for pyrolysis at 1050 °C in the presence of H 2 /N 2 .…”
Section: Methods Of Bcn Synthesismentioning
confidence: 99%
“…ASC achieved a high energy density/power density of 36.3 mW h cm −2 /3.2 mW cm −2 with 87% capacitance retention and 96% Coulombic efficiency. [ 36 ]…”
Section: Supercapacitor Application Of Bcn Heteroatom‐doped Bcn and B...mentioning
confidence: 99%
See 1 more Smart Citation
“…Another alternative type of electrode material platform for the assembly of BCN-based SCs is 3D nanostructured materials. Compared with 1D and 2D nanomaterials, the infinite growth from 3D features in their spatial structure make 3D BCN-based nanomaterials possess abundant active sites and porous-and-loose characteristics, which is beneficial for supercapacitors with high capacitance performance [118,119]. Tabassum et.al reported a BCNNT architecture entangled on a 3D melamine-foam-derived carbon skeleton with high surface area and hierarchical porosity which displayed a large capacitance of 344 F g −1 at a current density of 1 A g −1 [120].…”
Section: D Bcn-based Electrode Materialsmentioning
confidence: 99%
“…As researchers strive to identify the ideal material for supercapacitors, they are increasingly exploring hybrid topologies and synergistic composites to overcome the limitations of individual materials and achieve improved performance metrics. 41 Synergistic composites exhibit enhancements in energy density, power density, and cycle stability. These improvements are achieved by meticulously integrating diverse components possessing complementary qualities.…”
Section: Introductionmentioning
confidence: 99%